Analysis of research trends and development prospects of soluble guanylate cyclase stimulators/activators: using bibliometric methods - Yan, Bing Ju; Zhang, Jing; Wang, Jun; Yuan, Hong Xia (Frontiers in Pharmacology, 2025)
BackgroundThe stimulation and activation of soluble guanylate cyclase (sGC) has been a prominent focus of study in recent years. Currently, sGC stimulators/activators have a wide range of applications in various fields. However, there remains a gap in bibliometric analysis on this topic. We aim to visualize the research hotspots and trends in the field of sGC stimulators or activators. This analysis can equip researchers to understand current findings and forecast future trends efficiently.MethodsThe researchers searched for publications on sGC stimulators or activators in Web of Science Core Collection (WoSCC) on 22 July 2024. We then organized and analyzed the data using Microsoft Excel, online tool (Weishengxin), R, VOS viewer, and CiteSpace.Results1,879 papers from WoSCC were gathered for analysis, comprising 1,582 articles and 297 reviews. The United States is the most productive country. And Germany stands out as the country with the most robust collaboration. The most productive institution is BAYER AG. Furthermore, the majority of journals with citation frequencies in the top 10 belong to Q1. The Professor Stasch, JP is the most prolific author and the top co-cited author. Currently, the influential keywords include “riociguat”, “outcome”, “guanylate cyclase stimulator”, “heart failure”, “natriuretic peptide”, “vericiguat”, “reduced ejection fraction”, “mortality” and “placebo”.ConclusionThe future research hotspots will focus on the following aspects based on the current research hotspots: the safety verification of riociguat, the clinical efficacy of vericiguat for other types of heart failure, the role of praliciguat in diabetes nephropathy, and the efficacy and safety of newly discovered drugs. Furthermore, actively exploring new therapeutic directions for sGC stimulators or activators may also be an important trend in the future development of this field.